PENGARUH PROFESIONALISME, KEPUASAN KERJA, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEMERIKSA PAJAK (Studi Pada Pemeriksa Pajak KPP Pratama Bangkinang, KPP Pekanbaru Senapelan, KPP Pratama Pekanbaru Tampan, dan KPP Madya Pekanbaru) - Matheus, Evan; Zirman, Zirman; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research objective was examined the influenceof profesionalism, job satisfaction, motivation and work environment on the performanxe tax inspectors (study of tax inspectors in kpp pratama bangkinang, kpp prarama pekanbaru senapelan, kpp pratama pekanbaru tampan, kpp madya pekanbaru)The data in this study is the primary data. The population in this study were the tax auditors who worked at KPP Pratama Bangkinang, KPP Pratama Pekanbaru Senapelan, KPP Pratama Tampan, and KPP Pratama Madya Pekanbabru.The sampling method used in this study census method. The sample used in this study were60 respondents. The method of data analysis used to the test the hypotesis is multiple regression analysis using SPSS version 21.The results of this studyprofesionalism, job satisfaction, motivation and work environmentis showed influence on the tax auditors performance. The magnitude of the effect caused by Adjusted R² by three variables is 89% of the dependent variable, while the remaining 11% is influenced by other independent variabel that are not observed in this study.Keywords: Profesionalism, job satisfaction, motivation and work environment.